Prenatal and early postnatal depression and child maltreatment among Japanese fathers. (August 2017) - Takehara, Kenji; Suto, Maiko; Kakee, Naoko; Tachibana, Yoshiyuki; Mori, Rintaro
Abstract: We investigated the association of paternal depression in the prenatal and early postnatal period with child maltreatment tendency at two months postpartum among Japanese fathers. This population-based longitudinal study recruited Japanese perinatal women and their partners living in Nishio City, Aichi, Japan. Of the 270 fathers who participated, 196 were included in the analysis. All data were collected via self-administrated questionnaires at four time points: 20 weeks' gestation and in the first few days, one month, and two months postpartum. Paternal depression was assessed using the Edinburgh Postnatal Depression Scale. Three definitions of paternal depression were coded based on participants' scores on this measure: prenatal, prior, and current. Child maltreatment tendency was evaluated using the Child Maltreatment Scale at two months postpartum. The associations of the three definitions of paternal depression and child maltreatment tendency were separately analyzed using logistic regression analysis. The prevalence of prenatal, prior, and current paternal depression was 9.7%, 10.2%, and 8.8%, respectively. According to the multivariate analysis, current paternal depression was significantly associated with child maltreatment tendency at two months postpartum (adjusted odds ratio: 7.77, 95% CI: 1.83–33.02). The other two types of depression, however, were not related to child maltreatment tendency. Thus, current paternal depression increased the risk of child maltreatment tendency in the postnatal period, suggesting that early detection and treatment of paternal depression might be useful for the prevention of child maltreatment.